Granulomatosis with polyangiitis: clinical characteristics and updates in diagnosis - Potentas-Policewicz, Malgorzata; Fijolek, Justyna (Frontiers in Medicine, 2024)
Granulomatosis with polyangiitis (GPA) is a rare systemic disease characterized by granulomatous inflammation of the respiratory tract and necrotizing vasculitis of small and medium vessels often associated with the production of anti-neutrophil cytoplasmic antibodies (ANCA) directed mainly against leukocyte proteinase 3 (PR3). Usually, it involves upper airways, lungs, and kidneys, however any organ may be affected. The diagnosis is based on clinical, radiological, and serological findings. Biopsies, although strongly recommended, are not always feasible and often provides non-specific features. ANCA plays a crucial role in the diagnosis of GPA; nevertheless, ANCA detection is not a substitute for biopsy, which plays an important role in suspected cases, particularly when histological confirmation cannot be obtained. Significant advances have been made in classification criteria and phenotyping of the disease, particularly in determining the nuances between PR3-ANCA and myeloperoxidase (MPO)-ANCA vasculitis. This has led to better characterization of patients and the development of targeted treatment in the future. In addition, better identification of cytokine and immunological profiles may result in immuno-phenotyping becoming a new approach to identify patients with ANCA-associated vasculitis (AAV). Due to the chronic relapsing–remitting nature, strict follow-up of GPA is necessary to provide appropriate management. The search for the accurate marker of disease activity and to predict relapse is still ongoing and no predictor has been found to reliably guide therapeutic decision-making.